Zahlentheorie und Zahlenspiele : Sieben ausgewählte Themenstellungen. - Menzer, Hartmut (De Gruyter Studium., 2014)
<!Doctype html public ""-//w3c//dtd html 4.0 transitional//en""> This textbook presents the basic fundamentals of number theory along with more complex topics drawn from analytic and algebraic number theory. Each chapter includes a broad range of examples, study exercises with solutions, illustrations, and detailed presentations of proofs, making this book especially well-suited for examination preparation.